Educational workshop - Jau, Pauline (Universiti Teknologi MARA, Sarawak, 2006)
The Part 4 students from the Faculty of Office Management and Technology successfully organised a half-day Educational Workshop for all Pre-Commerce (69), DOM 1 (43), and DOM 2 (22) students on 24 September 2005. This event was conducted to fulfill the course requirement of Organising Skills (SSC290). The event was held at Auditorium 2, Block G, from 8:00 a.m. - 1:30 p.m. The theme for the workshop was "Sharpen Your Knowledge Widen Your Dreams". Two motivational speakers were invited - 'Study Skills' by Mr. Haikai Hammad Zin (UiTMCS), and 'Managing the Stresses of College Life' by Assoc Prof. Zainal Ariffin Zainuddin (YBLE Resources Sdn Bhd.). The event was organised to help participants achieve good results and become successful in their studies.